Kebijakan Kharaj Pada Masa Umar Bin Khattab Serta Kaitannya Dengan Pajak Bumi Dan Bangunan Di Indonesia - Agustin Mila Arlina; Windy Dwi Zhelsa Fithri; Dita Nur Amaliatul Chusniah (Institut Agama Islam Miftahul Ulum Pamekasan, 2025)
This study aims to comprehensively examine fiscal policy during the reign of Caliph Umar ibn Khattab, with particular attention to the implementation of land tax (kharaj) as an instrument of Islamic state revenue, and to examine its relevance to the Indonesian taxation system, particularly the Land and Building Tax (PBB). This study uses a qualitative method with a literature review approach, utilizing books, journals, and various relevant literature on kharaj and national taxation. The results indicate a conceptual alignment between kharaj and PBB, particularly in the mechanism for registering taxable objects, setting rates based on land conditions, and the function of tax as a source of state revenue. In Indonesia, PBB is regulated by Law Number 12 of 1994 with a self-assessment system and tax calculations based on the Taxable Object Sales Value (NJOP). This study concludes that Umar ibn Khattab's kharaj policy is not only historically relevant but also provides a philosophical and normative foundation for modern understandings of tax justice, wealth distribution, and state fiscal management.